2022
DOI: 10.1149/10701.4703ecst
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Teachers Well Being and Professional Commitment

Abstract: This article focuses on exploring the relationship between teachers well being and professional commitment. The investigator employed quantitative descriptive study and data was taken from 200 (50 male and 50 female) secondary school teachers from government schools and (50 male and 50 female) from private schools through scales of well being (1) and professional commitment scale (2) from Punjab state. The results found a positive and significant correlation of well being with the professional commitment of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Studies underscore the benefits of well-being programs in reducing stress and improving outcomes for both teachers and students (Carroll et al, 2021;Yang et al, 2022). Prioritizing teachers' emotional well-being fosters dedication and effectiveness (Abrol et al, 2022;Stark et al, 2022;Kuo, 2022).…”
Section: Hi Ghmentioning
confidence: 99%
“…Studies underscore the benefits of well-being programs in reducing stress and improving outcomes for both teachers and students (Carroll et al, 2021;Yang et al, 2022). Prioritizing teachers' emotional well-being fosters dedication and effectiveness (Abrol et al, 2022;Stark et al, 2022;Kuo, 2022).…”
Section: Hi Ghmentioning
confidence: 99%
“…Comparatively, data about the outcomes of teacher well-being are rather scarce, as not many investigations have considered teacher well-being as an outcome construct. Only a few studies have been conducted on the effect of teacher well-being on their work commitment (Abrol et al, 2022;Hu et al, 2022). Heidari et al (2022) concluded that psychological well-being and spiritual health can predict organisational commitment as a dependent variable among teachers.…”
Section: Teacher Well-beingmentioning
confidence: 99%
“…Comparatively, data about the outcomes of teacher well‐being are rather scarce, as not many investigations have considered teacher well‐being as an outcome construct. Only a few studies have been conducted on the effect of teacher well‐being on their work commitment (Abrol et al., 2022; Hu et al., 2022). Heidari et al.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation